P3.1 SUB-MAXIMAL EXERCISE BLOOD PRESSURE RELATES TO LEFT VENTRICULAR MASS INDEX, BUT IS DEPENDENT ON LOW AEROBIC CAPACITY - Martin Schultz*; Dean Picone; Rachel Climie; Costan Magnussen; Leah Wright; Thomas Marwick; Alison Venn; James Sharman (Artery Research, 2015)
Background: Exaggerated blood pressure (BP) responses to sub-maximal exercise independently predict cardiovascular (CV) events, mortality and incident hypertension. The aim of this study was to explore relationships between exercise BP, left-ventricular (LV) structure and function and aerobic fitness as potential mechanisms underlying the CV risk associated with sub-maximal exercise BP. Methods: 149 participants aged 40±2 years, 45% male completed a staged cycle test to estimate physical work capacity (aerobic fitness; PWC170) with concomitant BP measured each two minutes. 2D echocardiography was used to quantify LV mass (obtained from 2D-guided M-mode echo), and LV function (longitudinal strain, haemodynamics). Results: Early-stage exercise systolic BP was associated with aerobic fitness and LV mass index (r=0.22, and 0.24, p<0.05) and was greater in those performing high stage-relative work (high-fitness) compared with low stage-relative work (low-fitness) (154±22 vs. 133±15 mmHg, p<0.001). The high-fitness group had greater stroke volume, lower heart rate and LV longitudinal strain compared to the low-fitness group (72±18 vs. 59±15 ml, 61±9 vs. 68±9 bpm, −18±4 vs. −20±3%, p<0.05 for all). Exercise systolic BP was associated with LV mass index independent of resting BP, age and sex in the low-fitness group during stage one of the PWC170 (β=0.13, 95% CI=0.01-0.3) but not in the high-fitness group at any stage. Conclusions: Sub-maximal exercise systolic BP independently relates to LV mass index in those with low, early stage-relative aerobic capacity. BP measured during submaximal exercise testing (light-intensity) may reveal early changes in hypertension-related organ damage that are more evident in people with low-fitness.